Students’ Perceptions Toward Digital Narrative Approach in Reading Comprehension - Daffa Nirwana Wahyudi; Mardiatun Nissa; Siti Aulia Sintia; Naf’an Tarihoran (LPPM Universitas Islam Darul `Ulum Lamongan, 2026)
This study investigates students' perceptions of digital narrative approaches in enhancing English reading comprehension, motivation, and engagement at SMK Letris Indonesia, tackling challenges like limited vocabulary and monotonous traditional methods. A mixed-methods explanatory sequential design collected quantitative questionnaire data showing high